Integration and convergence of communication and information technologies as a motto in the learning-teaching process in the discipline of agricultural botany - Paranhos, Juçara Terezinha (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
In recent years we have noticed a loss of motivation on the part of students in the undergraduate classroom, reflecting on the teaching staff and negatively discouraging in the teaching/learning process, increasing the number of Deprecations in the disciplines and/or abandonment of the courses in which they are inserted. Thus, the work aimed to Investigate the contribution of conventional Allied pedagogical practices to information and communication technology resources as mediators and motivating in this process to students of undergraduate degree in agronomy from UFSM. The study was carried out in the first half of 2012, in school discipline BLG 1035-Agricultural Botany, with two repetitions (classes 11 and 12), with 21 students each. In the first quarter, the two classes were given the programmatic content of the discipline at the pedagogic project of the course, as well as the evaluations in the conventional way (100% attendance). In the second quarter, the content has been developed as an integrated distance mode in person, mediated by Moodle (Modular Object-Oriented Dynamic Learning Environment) and content assessments had consisted of in-person and virtual activities, with equal weights (50% each). In addition, at the end of the semester, were developed three other forms of evaluations: 1 evaluation of the questionnaire) and student teaching, in order to identify the level of use of the communication and information technologies (ICTs) via Moodle as motivational mediator in the teaching-learning process; 2 evaluation questionnaire) students, in order to evaluate the influence of the use of technology as a mediator motivational in teaching-learning process and compare to the conventional use of teaching contents by lecturer. In addition, identify the advantages and the difficulties encountered by them in using the virtual environment in the teaching-learning process; 3) student achievement considering the evaluations in face-to-face and distance mode. The two classes had averages above 7.0 on the level of competence and skill of the use of information and communication technology applied to education. As for the use of ICTs as motivating in the teaching-learning process we observed differences in views between the two groups, with the notes awarded by class 11 below 7.0, as opposed to class 12, with grades above 8.0. For class 11, the use of technologies mediated by Moodle in the presentation of the discipline has not contributed to the improvement in the teaching-learning process. These differences between the classes 11 and 12 were also highlighted in the evaluations of content and activities in presential and distance modalities, throughout the semester, with the smallest observed notes in class 11, contributing to the disapproval of six students in this class. There was no Deprecations in class 12.